Synthesis of Tetrahydro Pentagavunon-0 - Ritmaleni, Ritmaleni; Simbara, Ari (Indonesian Journal of Pharmacy, 2010)
Curcumin,  tetrahydrocurcumin,  and  monoketone  curcumin  analogue, pentagamavunone-0  (PGV-0),   have  been  investigated  as  antioxidant,  antiinflammatory  and  anticancer.  This  research  was  aimed  to  synthesise  the Tetrahydropentagamavunone-0  (THPGV-0)  compound  which  assumed  as  an active  metabolite  of  PGV-0.  The  hydrogenation  reaction  was  applied  to  the synthesis  of  THPGV-0  from  PGV-0  using  Pd/C  10  %  as  catalyst  at  room temperature.  The structure elucidation  was  analysed by  using  spectroscophy method. The synthetic result showed that THPGV-0 asa white crystalline powder in 25 % with melting point about 122-123 oC.Key words: pentagamavunone-0, Tetrahydropentagamavunone-0, hydrogenation